2007
DOI: 10.1103/physrevlett.98.246401
|View full text |Cite
|
Sign up to set email alerts
|

Critical Test for Altshuler-Aronov Theory: Evolution of the Density of States Singularity in Double PerovskiteSr2FeMoO6with Controlled Disorder

Abstract: With high-resolution photoemission spectroscopy measurements, the density of states (DOS) near the Fermi level (EF) of double perovskite Sr2FeMoO6 having different degrees of Fe/Mo antisite disorder has been investigated with varying temperature. The DOS near EF showed a systematic depletion with increasing degree of disorder, and recovered with increasing temperature. AltshulerAronov (AA) theory of disordered metals well explains the dependences of the experimental results. Scaling analysis of the spectra pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 20 publications
2
17
2
Order By: Relevance
“…The decrease in intensity at with the decrease in temperature may arise due to the disorder induced localization of the electronic states. Altshuler & Aronov showed that the charge disorder in a correlated system leads to dependence of the density of states near Fermi level20, which has been proved employing photoemission spectroscopy2122. In the present case, a plot of SDOS with shown in Fig.…”
Section: Resultssupporting
confidence: 52%
“…The decrease in intensity at with the decrease in temperature may arise due to the disorder induced localization of the electronic states. Altshuler & Aronov showed that the charge disorder in a correlated system leads to dependence of the density of states near Fermi level20, which has been proved employing photoemission spectroscopy2122. In the present case, a plot of SDOS with shown in Fig.…”
Section: Resultssupporting
confidence: 52%
“…The Altshuler-Aronov theory for interacting disordered metals [19] predicts that density of states near the Fermi level is a nonzero constant plus an anomalous power law contribution (in 3D) [21]. However, we can dismiss this assignment since our measured DOS extrapolates to zero at the Fermi level even though the samples are good conductors.…”
Section: Prl 118 097002 (2017) P H Y S I C a L R E V I E W L E T T Econtrasting
confidence: 40%
“…097002-3 disorder and electron interactions may also deplete the DOS near the Fermi level [18,19], which has recently been proposed for the interpretation of ARPES spectra [20,21]. The Altshuler-Aronov theory for interacting disordered metals [19] predicts that density of states near the Fermi level is a nonzero constant plus an anomalous power law contribution (in 3D) [21].…”
Section: Prl 118 097002 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…According to the Altshuler-Aronov theory2744, the interaction-induced correction to single-particle DOS in a three-dimensional metal assumes the form δν(ε) =  a  +  b |ε| 1/2 at k B T  < |ε| <  ħ /τ <  E F , where ε is the quasiparticle energy with respect to E F , and τ is the momentum relaxation time. The sign and magnitude of a and b are determined by mutually compensating interference effects in the singlet and triplet particle-hole diffusion channels454647.…”
Section: Resultsmentioning
confidence: 99%